Materials Science and Technology 2013
DOI: 10.1002/9783527603978.mst0396
|View full text |Cite
|
Sign up to set email alerts
|

Passivity of Metals and Alloys

Abstract: The sections in this article are Introduction Electrochemical Characteristics of Passive Systems Current–Potential Curves Thermodynamic Aspects of Passivity Potential Drops at the Passivated Surface Chemical Composition and Thickness of Passive Films on Metals Iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 135 publications
0
18
0
Order By: Relevance
“…The oxide is, furthermore, chemically and most-likely structurally different from the usual native oxide. The oxide is protective if it is dense and well-structured without any defects or with low defect density, sustaining also low in ionic as well as electronic conductivity [13,14]. However, the ‘rapid’ manufacturing (quenched melted surface) is associated with a large in-built dislocation density which may be similar to highly deformed microstructures.…”
Section: Characteristics Of Additively Manufactured Materialsmentioning
confidence: 99%
“…The oxide is, furthermore, chemically and most-likely structurally different from the usual native oxide. The oxide is protective if it is dense and well-structured without any defects or with low defect density, sustaining also low in ionic as well as electronic conductivity [13,14]. However, the ‘rapid’ manufacturing (quenched melted surface) is associated with a large in-built dislocation density which may be similar to highly deformed microstructures.…”
Section: Characteristics Of Additively Manufactured Materialsmentioning
confidence: 99%
“…The bulk chemical composition of the two phases are different, and ferrite is typically rich in Cr and Mo while austenite is rich in Ni, Mn and N, resulting in usually higher corrosion potentials for the austenite than the ferrite. 20,21 Ni is known to propel Cr and Mo towards the outermost surface, 5,22,23 which may further explain the higher nobility (and also the nobler corrosion potential) of the austenite than that of the ferrite despite its lower bulk concentrations of Cr and Mo (Fig. 1).…”
Section: Nobility Of Phasesmentioning
confidence: 99%
“…26 The passive film of stainless steels is known to be composed of an outer iron-rich oxide, mainly Fe 2 O 3 and Fe(OH) 2 /Fe(OH) 3 , and an inner chromiumrich oxide, often stated as Cr 2 O 3 and Cr(OH) 3 , with also some molybdenum as well as silicon species. [22][23][24]27 The composition and morphology as well as defect contents and semiconductor properties of passive films of stainless steel can largely differ depending on the environment in which they form. In earlier work, it was shown that the native passive film on the studied alloy gets more defective upon anodic polarisation from its passive to transpassive potential regime in 1 M NaCl solution, and becomes thicker and changes its composition and structure.…”
Section: Effect Of Nitric Acid Oxidation On the Passive Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Detailed understanding of tribocorrosion properties of passivated metals requires not only a good knowledge of the composition and structure of passivated surfaces and their dissolution mechanism in the absence of the second body but also a clear understanding of the behavior of metal surfaces in the active state and of the modifications generated by ion adsorption and by the active/passive transition. The topics addressed in this chapter include the adsorption of salt ions from the electrolyte and its influence on the dissolution of metal surfaces in the active state, the adsorption…”
Section: Introductionmentioning
confidence: 99%